Integral assessment of safety of potable waters in a finishing point of consumption - A. Tunakova, Yulia; V. Novikova, Svetlana; N. Gabdrakhmanova, Gulnara; I. Fayzulin, Rashat (International Conference “Environmental Engineering”, 2017)
The approach for integral assessment of potable waters with use of methods of the cluster analysis based on assessment of probability of intake of cations and anions of impurity with potable water and probabilities of carcinogenic and not carcinogenic changes in the state of health of the children’s population is offered.